SEKTOR INFORMAL PENJUAL ES TEBU DIDESA BUKIT PEDUSUNAN KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Alni Fitri; Teguh Widodo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The informal sector is a business that has a small scale with the aim of getting a job or job vacancy in order to earn income and not under the auspices of the government. This study serves to describe the survival strategy of the ice cane seller in the village of Bukit Pedusunan, Kuantan Mudik District, Kuantan Singingi Regency, where the ice cane seller uses his family members to help sell so that they no longer hire employees, increase working hours, and look for crowds in trading so that their needs life can be fulfilled. In addition, they also save on expenses, save the rest of the trade, and add to the network. Good network with sugarcane suppliers, fellow sellers, with buyers, and with the surrounding community. This research uses descriptive qualitative research method. Data collection techniques using observation, documentation, and in-depth interviews. The results of the research obtained, the researchers said that even though they only sell sugarcane ice on the sidewalk, they can still survive and meet the needs of their families and the cost of education for their children.  Keywords: Informal Sector, Survival Strategy, Family Needs